2003
DOI: 10.1038/sj.npp.1300276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Dopamine D3 Receptor Ligand, BP 897, on Acquisition and Expression of Food-, Morphine-, and Cocaine-induced Conditioned Place Preference, and Food-seeking Behavior in Rats

Abstract: The present study addressed the role of dopaminergic D 3 receptors (D 3 R) in motivational processes in rats. The effects of the selective D 3 R partial agonist, BP 897 (0.25-1 mg/kg, i.p.), on the establishment and the expression of conditioned place preference (CPP) supported by food, morphine (4 mg/kg, s.c.), or cocaine (2 mg/kg, s.c.) were investigated using an unbiased, one-compartment, placeconditioning procedure. When administered alone, BP 897 (0.05-2 mg/kg, i.p.) did not support CPP; on the contrary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 64 publications
3
65
2
Order By: Relevance
“…This is consistent with previous studies demonstrating that haloperidol (a preferential D 2 vs D 3 receptor antagonist) and raclopride (a mixed D 2 /D 3 receptor antagonist) have dysphorigenic or aversive properties in both humans and laboratory animals (Singh et al 1996;Kita et al 1999;Baldo et al 1999; see review by Platt et al 2002). This is also consistent with previous studies demonstrating that BP-897 produces an aversive-like effect, as assessed in the BSR and conditioned place preference/aversion paradigms (Duarte et al 2003;Gyertyán and Gál 2003;Campos et al 2004). In addition, BP-897 also produces a compensatory increase in cocaine self-administration (Gyertyán and Gál 2003), and inhibits quinpirole (a mixed D 2 / D 3 receptor agonist)-induced inhibition of DA neuronal firing in the substantia nigra, similar to the D 2 receptor antagonist haloperidol (Wicke and Garcia-Ladona 2001).…”
Section: Bp-897 Has Anti-addictive and Other Unwanted Effectssupporting
confidence: 92%
“…This is consistent with previous studies demonstrating that haloperidol (a preferential D 2 vs D 3 receptor antagonist) and raclopride (a mixed D 2 /D 3 receptor antagonist) have dysphorigenic or aversive properties in both humans and laboratory animals (Singh et al 1996;Kita et al 1999;Baldo et al 1999; see review by Platt et al 2002). This is also consistent with previous studies demonstrating that BP-897 produces an aversive-like effect, as assessed in the BSR and conditioned place preference/aversion paradigms (Duarte et al 2003;Gyertyán and Gál 2003;Campos et al 2004). In addition, BP-897 also produces a compensatory increase in cocaine self-administration (Gyertyán and Gál 2003), and inhibits quinpirole (a mixed D 2 / D 3 receptor agonist)-induced inhibition of DA neuronal firing in the substantia nigra, similar to the D 2 receptor antagonist haloperidol (Wicke and Garcia-Ladona 2001).…”
Section: Bp-897 Has Anti-addictive and Other Unwanted Effectssupporting
confidence: 92%
“…Disruption of dopamine function by administration of dopamine receptor antagonists impairs Pavlovian conditioning (Di Ciano et al, 2001;Duarte et al, 2003;Parkinson et al, 2002;Spyraki et al, 1982). However, in the current study, both DAT KD and WT mice acquired anticipatory responses to the cue light that was associated with the food at similar rates.…”
Section: Mice With Chronically Elevated Dopamine Exhibit Normal Acquicontrasting
confidence: 55%
“…Disruption of dopamine function by administration of dopamine receptor antagonists impairs acquisition of food conditioned place preference (Duarte et al, 2003;Spyraki et al, 1982), Pavlovian approach behavior (Di Ciano et al, 2001;Parkinson et al, 2002), and lever pressing for a food reward (Smith-Roe and Kelley, 2000;Wise and Schwartz, 1981). Moreover, it has been shown that dopamine neuron firing correlates with reward-related learning (Roitman et al, 2004;Schultz, 2002) perhaps by modulating synaptic plasticity (Calabresi et al, 1992;Centonze et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…BP-897 significantly decreases the discriminative stimulus effects of D-amphetamine and cocaine [21] and attenuates the expression and acquisition of the CPP response to cocaine without altering the acquisition or expression of the CPP response to food or morphine [88]. However, BP-897 alone produced CPA, a finding congruent with that of Gyertyán and Gál [121], and may also have anxiolytic properties [246].…”
Section: Receptor Agonistsmentioning
confidence: 96%